Total volume versus bouts: prospective relationship of physical activity and sedentary time with cardiometabolic risk in children. Issue 10 (October 2018) - Chinapaw, Mai; Klakk, Heidi; Møller, Niels; Andersen, Lars; Altenburg, Teatske; Wedderkopp, Niels
Abstract Background/objectives Examine the prospective relationship of total volume versus bouts of sedentary behaviour (SB) and moderate-to-vigorous physical activity (MVPA) with cardiometabolic risk in children. In addition, the moderating effects of weight status and MVPA were explored. Subjects/methods Longitudinal study including 454 primary school children (mean age 10.3 years). Total volume and bouts (i.e. ≥10 min consecutive minutes) of MVPA and SB were assessed by accelerometry in Nov 2009/Jan 2010 (T1) and Aug/Oct 2010 (T2). Triglycerides, total cholesterol/HDL cholesterol ratio (TC:HDLC ratio), homoeostatic model assessment of insulin resistance, systolic blood pressure and waist circumference were assessed at T2 (Sept/Oct 2010) and combined in a composite cardiometabolic risk score. Associations of total time and uninterrupted MVPA and SB were examined using multilevel mixed linear models, with or without mutual adjustments between MVPA and SB. The moderating effects of weight status and MVPA (for SB only) were examined by adding interaction terms. Results Children engaged daily in about 60 min of total MVPA and 0–15 min/week in MVPA bouts. Mean total sedentary time was around 7 h/day with over 3 h/day accumulated in bouts. Higher mean levels of MVPA were significantly associated with a lower waist circumference, triglycerides, insulin resistance, TC:HDLC ratio and composite cardiometabolic risk, with non-significant associations for uninterrupted MVPA. Associations with sedentary time were much smaller and inconsistent: higher total sedentary time was associated with higher insulin resistance; after adjusting for MVPA, higher mean total and bouts of sedentary time were associated with lower waist circumference, and sedentary bouts with lower composite cardiometabolic risk. Conclusions Children accumulated MVPA intermittently and rarely in bouts, and about half their total sedentary time in bouts. Total MVPA is important for lowering cardiometabolic risk in children, whereas both total and uninterrupted sedentary time seem of less importance.